Determinants of TB/HIV coinfection-related deaths audited using the TB death checklist from health facilities in Rwanda - Mutembayire et al. (Rwanda Medical Journal)
INTRODUCTION: Tuberculosis (TB) remains a public health threat worldwide, mainly affecting countries with low-resource settings, including Rwanda. TB/HIV coinfection increases the severity of TB and has a high of resulting in poor outcomes, such as death. This study aims to investigate the actual causes and factors associated with mortality among TB/HIV coinfected patients in Rwanda, to better understand the profile of deaths in this population.